Konseling Adlerian dalam Mengidentifikasi Penanganan Harga Diri - Oetari, Aiuningtyas Yuni; Nishafa, Difani Khoirun; Susanto, Adianna Muthia; Alhabsyi, Bakhrudin (Advice: Jurnal Bimbingan dan Konseling, 2024)
Adlerian counseling is a part of personality theory that focuses on self-esteem. In Adlerian counseling, there are various factors that can influence a person's personality, namely: life goals, lifestyle, creative power, feelings of inferiority, existential urges, social encouragement as well as inferior and superior. Self-esteem is an overall view and assessment of oneself that is sometimes in accordance with one's own wishes. The aim of this research is to understand feelings of low self-esteem and treatment that focuses on individual feelings and self-esteem. The results of this research include: 1. Emphasizing the importance of understanding social influences on the development of individual self-esteem; 2. This counseling emphasizes understanding individuals who are influenced by behavior and social relationships; 3. This counseling focuses on building self-confidence and adjusting thought patterns to be more positive.